Skeletal muscle deficits are associated with worse exercise performance in pediatric pulmonary hypertension - Avitabile, Catherine M.; McBride, Michael G.; Harris, Matthew A.; Whitehead, Kevin K.; Fogel, Mark A.; Paridon, Stephen M.; Zemel, Babette S. (Frontiers in Pediatrics, 2022)
Background: Skeletal muscle deficits are associated with worse exercise performance in adults with pulmonary hypertension (PH) but the impact is poorly understood in pediatric PH. Objective: To study muscle deficits, physical inactivity, and performance on cardiopulmonary exercise test (CPET) and exercise cardiac magnetic resonance (eCMR) in pediatric PH. Methods: Youth 8-18 years participated in a prospective, cross-sectional study including densitometry (DXA) for measurement of leg lean mass Z-score (LLMZ), handheld dynamometer with generation of dominant and non-dominant handgrip Z-scores, Physical Activity Questionnaire (PAQ), CPET, and optional eCMR. CPET parameters were expressed relative to published reference values. CMR protocol included ventricular volumes and indexed systemic flow at rest and just after supine ergometer exercise. Relationships between LLMZ, PAQ score, and exercise performance were assessed by Pearson correlation and multiple linear regression. Results: There were 25 participants (13.72.8 years, 56% female, 64% PH Group 1, 60% functional class I); 12 (48%) performed both CPET and eCMR. Mean LLMZ (-0.96±1.14) was associated with PAQ score (r=50, p=0.01) and with peak oxygen consumption (VO2) (r=0.74, p=<0.001), VO2 at anaerobic threshold (r=0.65, p<0.001), and peak work rate (r=0.64, p<0.01). Higher handgrip Z-scores were associated with better CPET and eCMR performance. On regression analysis, LLMZ and PAQ score were positively associated with peak VO2, while handgrip Z-score and PAQ score were positively associated with peak work rate. Conclusion Muscle mass and strength are positively associated with exercise performance in pediatric PH. Future studies should determine the effect of rehabilitation programs on muscle properties and exercise performance.